Editorial (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.5928.19-21.Apresenta a 2a. edição da Revista Gestão & Conexões (Management and Connections Journal), v2, n1, jan./jun. 2013.